PENGARUH ISLAMIC BRANDING DAN TREND FASHION TERHADAP KEPUTUSAN PEMBELIAN FASHION ISLAMI PADA MAHASISWA SURABAYA - Zulfa, Fina Lailiz; Fahrullah, (Universitas Negeri Surabaya, 2024)
Consumer demand for Islamic fashion products is increasing, particularly among students who care about the Islamic fashion industry that reflects the halal lifestyle. Students have a critical attitude when consuming fashion products. This study aims to determine the effect of Islamic branding and fashion trends on purchasing decisions for Islamic fashion in Surabaya students. This study uses a quantitative approach with multiple linear regression analysis techniques. The data used is primary data through distributing questionnaires. The research sample amounted to 100 respondents who were randomly selected based on certain criteria using purposive sampling technique. The results showed that Islamic branding and fashion trends partially affect Islamic fashion purchasing decisions. The results of testing the coefficient of determination obtained that Islamic branding and fashion trends have a simultaneous influence of 49.2% on Islamic fashion purchasing decisions. This research can provide insight to business people to develop more effective marketing strategies in order to achieve success in the Islamic fashion market